Lymphocyte Cell Ratios and Mortality among Incident Hemodialysis Patients - Catabay, Christina; Obi, Yoshitsugu; Streja, Elani; Soohoo, Melissa; Park, Christina; Rhee, Connie M; Kovesdy, Csaba P; Hamano, Takayuki; Kalantar-Zadeh, Kamyar (American journal of nephrology, 2017)
Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been previously suggested as oncologic prognostication markers. These are associated with malnutrition and inflammation, and hence, may provide benefit in predicting mortality among hemodialysis patients. Among 108,548 incident hemodialysis patients in a large U.S. dialysis organization (2007-2011), we compared the mortality predictability of NLR and PLR with baseline and time-varying covariate Cox models using the receiver operating characteristic curve (AUROC), net reclassification index (NRI), and adjusted R2. During the median follow-up period of 1.4 years, 28,618 patients died. Median (IQR) NLR and PLR at baseline were 3.64 (2.68-5.00) and 179 (136-248) respectively. NLR was associated with higher mortality, which appeared stronger in the time-varying versus baseline model. PLR exhibited a J-shaped association with mortality in both models. NLR provided better mortality prediction in addition to demographics, comorbidities, and serum albumin; ΔAUROC and NRI for 1-year mortality (95% CI) were 0.010 (0.009-0.012) and 6.4% (5.5-7.3%) respectively. Additionally, adjusted R2 (95% CI) for the Cox model increased from 0.269 (0.262-0.276) to 0.283 (0.276-0.290) in the non-time-varying model and from 0.467 (0.461-0.472) to 0.505 (0.500-0.512) in the time-varying model. There was little to no benefit of adding PLR to predict mortality. High NLR in incident hemodialysis patients predicted mortality, especially in the short-term period. NLR, but not PLR, added modest benefit in predicting mortality along with demographics, comorbidities, and serum albumin, and should be included in prognostication approaches.